SECRETORY STRUCTURES IN THE CAPITULA OF SANTOLINA LEUCANTHA BERTOL. (ASTERACEAE). MORPHOLOGY AND HISTOCHEMISTRY - PAGNI, A.M. (Annali di Botanica, 2019)
In the capitula of Santolina leucantha Bertol. two distinct types of secretory structures have been examined: secretory ducts and glandular trichomes. The ducts are rather variable both in their morphology and size; the trichomes are pluricellular and biseriate. The two structures have a quite different distribution: the glandular trichomes are present on the corolla and on the scales, the ducts are present in the stigma, in the scales and in the receptacle. The histochemical analyses of their secretion have revealed the presence of several compounds; although similar, the two secretions are partially different, in that they differ in the lipid composition; moreover peptic substances and tannins seem to be produced by glandular trichomes only.